The Effect Of Lifestyle, Financial Attitudes, And Personal Financial Literacy On Personal Financial Management Among Students - Fachri, Saeful; Kahpi, Heri Sapari; Miftarofah, Aaf Afmita (Tirtayasa Ekonomika, 2024)
This research was conducted (1) to determine lifestyle on student financial management (2) to determine the influence of financial attitudes on student financial management (3) to determine the influence of financial literacy on student financial management (4) to determine lifestyle, financial attitudes and literacy finance on student financial management. This type of research is a quantitative survey, with data collection techniques using secondary and primary data in the form of observations and questionnaires, the sample consisted of 99 FEB students from private universities in the city of Serang. The results of this research show that based on the results of hypothesis testing, lifestyle has a significant effect on student financial management. This is proven by tcount > ttable (3.188>1,984) with a significance of 0.002. hypothesis testing that financial attitudes have a significant effect on student financial management. This is proven by tcount > ttable (9.501>1,984) with a significance of 0.000, and testing the hypothesis that financial literacy has a significant effect on student financial management. This is proven by tcount > ttable (7.861>1.984) with a significance of 0.000. Meanwhile, simultaneously (together) there is a positive and significant influence between lifestyle variables, financial attitudes and financial literacy on financial management. with a value of Fcount>Ftable (67.158>2.70) and a sig value of F < α (0.000<0.05). And the results of multiple linear regression are Y = 700 + 0.160X₁ + 0.429X₂ + 0.389X₃. 68% while the remaining 32% is explained by other variables not included in this study.